Clinical outcomes of post‐renal transplant patients with COVID‐19 infection in the ICU: A single‐center case series. Issue 7 (23rd July 2021) - Shaikh, Nissar; Khatib, Mohamad Y.; Alwraidat, Mohammad A.; Ananthegowda, Dore C.; Othman, Muftah; Aroos, Asra; Jujjavarapu, Sagar B.; Banerjee, Saptarshi; Nasir, Zishan; Mohamed, Ahmed S.; Elshafei, Moustafa S.; Almaslamani, Muna A.; et al.
Abstract: Most of the post‐renal transplant patients are taking immunosuppressive medications, including calcineurin inhibitors, anti‐proliferative agents, and steroids. This case series highlights the clinical characteristics and outcomes of eight post‐renal transplant patients with severe COVID‐19 infection admitted to the intensive care unit. Abstract : There is a paucity of available literature regarding the impact of COVID‐19 infection in post‐renal transplant patients. These patients have a higher chance of acquiring severe COVID‐19 infection, more complications, and poor prognosis.